(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article discusses the cisterns and their construction, which were built in the territory of the Jizzakh oasis and occupied a worthy place on the trade caravan routes. The YYogocli, Mirzarabat and Yakka cisterns in the oasis are among the water structures that have solved the water-related problems of merchants and tourists during their operation.